2011
DOI: 10.1016/j.ejpain.2010.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Review: The influence of informal social support on risk and prognosis in spinal pain: A systematic review

Abstract: Spinal pain is very common and has considerable consequences for the individual (e.g. loss of employment, disability) as well as increased health care costs. It is now widely accepted that biological, psychological and social factors impact on spinal pain outcomes. The majority of research on social factors has been employment related, with little attention to the influence of informal social support (e.g. families, friends, social groups). The aim of this review is to investigate whether informal social suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 49 publications
(124 reference statements)
3
61
0
3
Order By: Relevance
“…It refers to the support people report having received or that is available to them if needed within the context of informal (e.g., family, friends) or formal relationships (e.g., healthcare services/professionals; Cohen et al 2000). Findings highlight the importance of social support in the experience of pain and pain-related outcomes such as disability (e.g., Campbell et al 2011;Campbell and Wynne-Jones 2013;Leonard et al 2006;Newton-John 2002). Most of this literature, however, has been focusing on the role of informal social support (from spouses or co-workers) on middle-aged adults' pain experiences.…”
Section: Introductionmentioning
confidence: 97%
“…It refers to the support people report having received or that is available to them if needed within the context of informal (e.g., family, friends) or formal relationships (e.g., healthcare services/professionals; Cohen et al 2000). Findings highlight the importance of social support in the experience of pain and pain-related outcomes such as disability (e.g., Campbell et al 2011;Campbell and Wynne-Jones 2013;Leonard et al 2006;Newton-John 2002). Most of this literature, however, has been focusing on the role of informal social support (from spouses or co-workers) on middle-aged adults' pain experiences.…”
Section: Introductionmentioning
confidence: 97%
“…With regard to pain research, evidence also suggests that social support may be an important factor in overcoming pain-related disability (e.g., Evers et al, 2003;Lee et al, 4 2015; Ziryanova et al, 2006). Nevertheless, evidence for the relationship between social support and pain-related disability is often inconsistent (see review by Campbell et al, 2011). Some studies have shown that high social support in chronic pain patients is associated with lower levels of painrelated disability and avoidance of daily activities (e.g., Cohen & Wills, 1985;Evers et al, 2003;Hughes et al, 2014;Jamison & Virts, 1990;Roberts, et al, 2015;Turk et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Cognitivebehavioural models have also been developed to explain this phenomenon, whereby the perceptions and thoughts of significant others are proposed to play an important role in pain adjustment as they translate into unhelpful behaviours such as solicitousness or punishment [25]. More recent research has begun to acknowledge the importance of self-regulation in this field, which suggests that significant others' own beliefs and meanings about pain may be particularly salient influences on their relative's persistent pain behavior and disability [26,27].…”
Section: Discussionmentioning
confidence: 99%